IGF antagonizes the Wnt/β-Catenin pathway and promotes differentiation of extra-embryonic endoderm - Schlupf, Judith; Steinbeisser, Herbert (Differentiation, 2014)
Mouse F9 teratocarcinoma cells are an established model for the differentiation of extra-embryonic endoderm (ExEn). Primitive endoderm, parietal and visceral endoderm can be generated by stimulation of F9 cells with retinoic acid and dibutyryl cyclic adenosine monophosphate. Here we show that Wnt/β-Catenin signaling is down-regulated during ExEn differentiation in F9 cells and that the inhibition of the Wnt pathway promotes differentiation of the three extra-embryonic endoderm lineages. Wnt inhibition is achieved through the IGF pathway, which is up-regulated during differentiation. IGF signaling antagonizes the Wnt pathway by stimulating transcription of axin2 and by stabilizing Axin1 protein. Both Axin1 and Axin2 are components of the β-Catenin destruction complex and act as intra-cellular inhibitors of the Wnt/β-Catenin pathway. The data presented reveal a mechanism which restricts pluripotency of undifferentiated cells and directs them toward extra-embryonic lineages.
Gesehen am 13.08.2020